Aging of a Lithium-Metal/LFP Cell: Predictive Model and Experimental Validation - Davide Dessantis; Piera Di Prima; Daniele Versaci; Julia Amici; Carlotta Francia; Silvia Bodoardo; Massimo Santarelli (Batteries, 2023)
Actual market requirements for storage systems highlight the limits of graphite as an anode for Li-ion batteries. Lithium metal can represent a suitable alternative to graphite due to its high theoretical specific capacity (about 3860 mAh g−1) and low negative redox potential. However, several aging mechanisms, such as dendrite growth, lithium loss and the formation of an unstable SEI, decrease the performances of Li-based batteries. A suitable strategy to better understand and study these mechanisms could be the development of an electrochemical model that forecasts the aging behaviour of a lithium-metal battery. In this work, a P2D aging electrochemical model for an Li-based cell was developed. The main innovation is represented by the combination of two aspects: the substitution of graphite with metallic lithium as an anode and the implementation of SEI growth on the metallic lithium surface. The calibration of the model, based on experimental measurements and the successive validation, led to us obtaining a good accuracy between the simulated and experimental curves. This good accuracy makes the developed P2D aging model a versatile and suitable approach for further investigations on Li-based batteries considering all the aging phenomena involved.